Occlusal Pressure Analysis of Complete Dentures after Microwave Disinfection: A Clinical Study - Basso, Michael Frederico Manzolli [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Vergani, Carlos Eduardo [UNESP]; Pavarina, Ana Cláudia [UNESP]; Machado, Ana Lúcia [UNESP]; Jorge, Janaina Habib [UNESP] (Wiley, 2017)
Purpose: This clinical study evaluated the effect of microwave disinfection protocols on the occlusal pressure pattern of dentures. Materials and Methods: Dentures were constructed for 40 patients and evaluated as follows (n = 20). Group 1: Patients had the maxillary dentures submitted to microwave disinfection, once a week, for 4 weeks. Group 2: Patients had the maxillary dentures submitted to microwave disinfection, three times a week, for 4 weeks. Occlusal contacts were recorded on five occasions: 30 days after denture insertion and before first disinfection (baseline or control group); 1 week after disinfection; 2 weeks after disinfection; 3 weeks after disinfection; 4 weeks after disinfection. Occlusal contacts were analyzed by T-Scan III. Intergroup analysis was performed using the Mann-Whitney test and intragroup analysis using the Friedman test with significance of 5%. Results: The results showed no significant difference between groups during the periods. The data on parameters loss of denture adaptation or complaints showed that patients used their dentures regularly for eating and expressed comfort and satisfaction in all experimental periods. The evaluation of functional occlusion revealed that the distribution of the occlusal contacts remained unaltered after disinfection. Conclusion: Microwave disinfection protocols as studied in this report did not influence occlusal contacts of the complete dentures.
Keywords: acrylic resin; clinical trial; Complete denture; disinfection; microwave; occlusal analysis; Tek scan III